EKLEKTISISME ANTARA HUKUM ISLAM DAN HUKUM UMUM: STUDI KRITIS ATAS GAGASAN AHMAD QODRI AZIZY DALAM MEWUJUDKAN HUKUM NASIONAL - Yudarwin Yudarwin Yudarwin (Ilmu Hukum Prima (IHP), 2018)
Indonesia currently does not have a legal pattern that reflects the personality of its people. The Act which is used as a law that applies, both in law and in the field of civilization is the acceptance of the inheritance of Dutch colonial law. Given this, the idea of realizing Indonesian national law is absolutely necessary. But how do you do it? Professor Ahmad Qodri Azizy, Ph.D, a figure who is an expert in the field of Islamic law tried to offer this idea in his book, National Law: Eclecticism in Islamic Law and General Law. In the book, it is explained that the eclecticism approach is a way of choosing which among the raw materials of national law consists of Islamic law, Western law and Customary law which is the best in realizing national law. Therefore, the problems examined in this study are; what is the concept of eclecticism in Islamic law and general law according to A. Qodri Azizy? This research is classified as a type of normative legal research that is descriptive-critical. In this study, data about the ideas of A. Qodri Azizy and the reasons behind the emergence of these ideas were explored as thoroughly as possible, then criticized to produce an assessment. The approach taken in this study is the historical approach and the comparative approach. These two approaches are expected to understand the history of Western law with the elements behind it; both in terms of thinking and philosophy, changes and developments, as well as positive and negative values of the similarities and differences in Islamic law and Western law. Because this research is also related to the idea of A. Qodri Azizy as a figure, this study also uses a critical-analytical approach, in which this approach will reveal the strengths and weaknesses of the ideas of A. Qodri Azizy regarding the legal eclecticism offered. Data analysis was carried out using constant comparative analysis, namely by concentrating the description of the ideas of A. Qodri Azizy with the problems discussed and comparing them with other data. And the results found from this study are; first, the concept of legal eclecticism initiated by A. Qodri Azizy in realizing national law was not just born.